What are the features of high-performing quality improvement collaboratives? A qualitative case study of a state-wide collaboratives programme - Mary Dixon-Woods; Justin B Dimick; Graham P Martin; Michael J Englesbe; James G McGowan; Greta L Krapohl; Darrell A Campbell (BMJ Open)
Objectives Despite their widespread use, the evidence base for the effectiveness of quality improvement collaboratives remains mixed. Lack of clarity about ‘what good looks like’ in collaboratives remains a persistent problem. We aimed to identify the distinctive features of a state-wide collaboratives programme that has demonstrated sustained improvements in quality of care in a range of clinical specialties over a long period.Design Qualitative case study involving interviews with purposively sampled participants, observations and analysis of documents.Setting The Michigan Collaborative Quality Initiatives programme.Participants 38 participants, including clinicians and managers from 10 collaboratives, and staff from the University of Michigan and Blue Cross Blue Shield of Michigan.Results We identified five features that characterised success in the collaboratives programme: learning from positive deviance; high-quality coordination; high-quality measurement and comparative performance feedback; careful use of motivational levers; and mobilising professional leadership and building community. Rigorous measurement, securing professional leadership and engagement, cultivating a collaborative culture, creating accountability for quality, and relieving participating sites of unnecessary burdens associated with programme participation were all important to high performance.Conclusions Our findings offer valuable learning for optimising collaboration-based approaches to improvement in healthcare, with implications for the design, structure and resourcing of quality improvement collaboratives. These findings are likely to be useful to clinicians, managers, policy-makers and health system leaders engaged in multiorganisational approaches to improving quality and safety.